Effect of osteotomy strategy on primary stability and intraosseous temperature rise: an ex-vivo study - Gözde Gökçe Uçkun; Sina Saygılı; Merve Çakır; Onur Geçkili (BMC Oral Health)
Abstract Background Primary stability is a perquisite for achieving successful osseointegration. Additionally thermal effect of implant bed preparation plays an important role in success of a dental implant. This ex vivo study was conducted to compare one step implant specific osteotomy and conventional osteotomy in terms of primary stability and thermal changes during surgery. Methods Forty eight implants were inserted into the sheep iliac crest bones each with a safe distance to each other and divided into six groups. In two of the groups implant specific osteotomy and in the remaining 4 groups conventional osteotomy was performed. In the groups, the primary stability of the trioval implants designed for the implant specific osteotomy were compared with the oval active threaded implants. The two osteotomy methods were also compared. Additionally the thermal changes during the two osteotomy methods were compared using a double-channel temperature monitoring device. Results Statistically significant differences (P <.05) were observed between the stability groups and the thermal evaluation groups (P <.05). Implant specific osteotomy revealed significantly higher stability than the conventional osteotomy (P <.001). Osteotomy without irrigation caused significantly higher thermal changes than the conventional osteotomy wit irrigation (P <.001). Conclusion Although the implant specific osteotomy reveals better primary stability, it causes higher temperature during drilling. However, since this increase is within the limits and doesn’t cause a risk in terms of osseointegration, it may be used safely in clinical practice.